Eosinophilic Dermatosis of Myeloproliferative Disease in a Young Adult With Diffuse Large B-Cell Lymphoma. (April 2019) - Jencks, Amy; Kiavash, Katrin; Daveluy, Steven; Thompson, Andrew D.
Abstract : Abstract: Exaggerated insect bite reactions present as exuberant papular and vesiculobullous lesions in patients with hematologic malignant neoplasms. The most commonly reported hematological malignancy with exaggerated insect bite reactions is chronic lymphocytic leukemia. Other reported reactions have been seen in patients with mantle cell lymphoma. Clinical presentation may vary with many patients unaware of a previous insect bite. Therefore, the terms "exaggerated bite-like reaction" and "eosinophilic dermatosis of myeloproliferative disease" have been proposed. The lesions may wax and wane or persist for many years, and they seem to be unrelated to the underlying hematologic disorder course or therapy. In some circumstances, the lesions may actually precede the diagnosis of the hematological malignancy. In this study, we describe a case of "eosinophilic eruption of myeloproliferative disease" associated with diffuse large B-cell lymphoma in a young adult. To the best of our knowledge, this is the first case reported in association with diffuse large B-cell lymphoma.